Investigating hybrid mesons with $$0^{+-}$$ 0 + - and $$2^{+-}$$ 2 + - exotic quantum numbers - Bing Chen; Xiang Liu (European Physical Journal C: Particles and Fields)
Abstract Hybrid mesons occupy a unique position in the hadronic spectrum, offering a valuable insight into the non-perturbative nature of the glue field. Hybrid states with exotic $$J^{PC}$$ J PC quantum numbers, such as the $$1^{-+}$$ 1 - + , $$0^{+-}$$ 0 + - and $$2^{+-}$$ 2 + - , cannot mix with conventional $$q\bar{q}$$ q q ¯ mesons, making them critical for establishing the full spectrum of hybrid mesons. In this work, we investigate the masses and the strong decays of $$0^{+-}$$ 0 + - and $$2^{+-}$$ 2 + - hybrid mesons, which could be regarded as the first orbitally excited states of the $$π _1(1600)$$ π 1 ( 1600 ) and $$η _1(1855)$$ η 1 ( 1855 ) mesons. We develop a constituent gluon model and apply it to study the mass spectra and decay modes of these exotic states. Our results suggest that experiment may searched for these $$0^{+-}$$ 0 + - and $$2^{+-}$$ 2 + - hybrid mesons in the mass region between 2.0 and 2.4 GeV. Additionally, we identify some key decay channels which should be targeted in future experiments.